Return to Play After a Lateral Ligament Ankle Sprain - P. D’Hooghe (14151954) (2022)
Purpose of Review The purpose of this review is to describe the current evidence on the most common sports-related ankle injuries. Joint anatomy, epidemiology, clinical findings, diagnostic approach, and treatment are presented with a specific focus on the available evidence towards return to play. Recent Findings Recent findings show that ankle sprain is the most common injury in the world of sports. Bony fractures, cartilage defects, and syndesmotic lesions are frequently seen in association with the more severe type of ankle sprains. Summary In summary, the majority of the athletes’ ankle sprains are managed conservatively with excellent outcomes and full return to their pre-injury level of play. However, it is essential to differentiate the single ligament sprain from a more complex injury to the ankle joint. The evidence-based treatment and rehabilitation programmes are associated with a better prognosis and a faster time to return to sport participation. Other Information Published in: Current Reviews in Musculoskeletal Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s12178-020-09631-1